Nitrogen fertilization and leaf spraying with Azospirillum brasilense in wheat: effects on mineral nutrition and yield - Besen, Marcos Renan; Goes Neto, Antonio Feijo; Esper Neto, Michel; Zampar, Eder Junior de Oliveira; Costa, Eunápio José de Oliveira; Cordioli, Vitor Rodrigues; Inoue, Tadeu Takeyoshi; Batista, Marcelo Augusto (Revista de Ciências Agroveterinárias, 2020)
The use of Azospirillum brasilense has the potential to improve plant nitrogen (N) use efficiency, while a better understanding of alternative management practices with inoculation is necessary. The aim was to examine the effects of the leaf application of A. brasilense in association with nitrogen fertilization on the wheat crop. The experiment was conducted in Lidianópolis, Paraná, Brazil, in a completely randomized block design with four replications. The treatments included four doses of A. brasilense for leaf application (0, 200, 400, and 600 ml ha-1) and four doses of N (0, 40, 80, and 120 kg N ha-1). The nutritional content, yield components, quality, and yield of the wheat crop were evaluated. There was no interaction among the factors, nor did the treatments have an isolated effect on spike length, the number of spikelets per spike, spikes per m2, thousand grain weight, and test weight. However, doses of A. brasilense increased calcium and magnesium absorption at 283 and 380 ml ha-1, respectively. Similarly, nitrogen application increased the content of calcium, magnesium, and copper in the leaf at 61, 47, and 49 kg N ha-1, respectively. Nitrogen also increased the number of grains per spike and yield at 56 and 54 kg N ha-1, respectively. Yield correlated with the number of grains per spike and the manganese and copper content in the leaf. The results demonstrate that the inoculation of leaves with A. brasilense favored a higher absorption of divalent cationic macronutrients and that N was fundamental to increasing the yield, with the best responses observed between 47 and 61 kg ha-1.